Promoting Effect of Horticultural Therapy on College Students’ Positive Psychological Quality - Li, Yong-ling; Li, Feng; Gui, Zhi; Gao, Wen-bin (Frontiers in Psychology, 2022)
To explore the effect of horticultural therapy on cultivating College Students’ positive psychological quality and to provide reference for college students’ mental health education, 176 college students were randomly divided into experimental group (n = 88) and control group (n = 88). The experimental group was intervened by horticulture therapy, and the Chinese college students’ mental health evaluation system and Chinese college students’ positive psychological quality scale were used to test the experimental group and the control group. There was no difference in the six dimensions of positive psychological quality between the experimental group and the control group in the pre-test. After 9 weeks of intervention, the differences between the experimental group and the control group in the “cognitive dimension” and “emotional dimension” were significant. The scores of emotional dimension and transcendental dimension in the experimental group were higher than those in the pre-test (all p < 0.05); meanwhile, there is no difference in the other four dimensions. Horticultural therapy can promote the positive psychological quality of college students.